2012
DOI: 10.3989/mc.2012.03211
|View full text |Cite
|
Sign up to set email alerts
|

Comparativa del comportamiento acústico entre fachadas multicapas ligeras y fachadas tradicionales

Abstract: RESUMENLos sistemas de fachadas multicapas ligeras acústica-mente, en general, han sido poco estudiados. Los primeros datos que se tienen es que no suelen alcanzar los valores de aislamiento acústico requeridos en el Código Técnico de la Edificación (CTE) en entornos especialmente ruidosos. Los objetivos principales de esta investigación son obtener fachadas multicapas ligeras con un alto grado de aislamiento acústico, que puedan ser empleados en entornos ruidosos. Al mismo tiempo que presenten excelentes cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The other three prototypes were multilayer lightweight façades: two with intermediate ventilated air cavity systems and one without an intermediate air cavity. The results indicated that the prototypes without an intermediate ventilated air cavity had better sound reduction but the systems with intermediate air cavities had good acoustic behaviour, above the requirements of Spanish acoustic regulation code CTE DB-HR (Ruiz, Delgado, Neila, & Vega, 2012).…”
Section: State Of the Artmentioning
confidence: 93%
“…The other three prototypes were multilayer lightweight façades: two with intermediate ventilated air cavity systems and one without an intermediate air cavity. The results indicated that the prototypes without an intermediate ventilated air cavity had better sound reduction but the systems with intermediate air cavities had good acoustic behaviour, above the requirements of Spanish acoustic regulation code CTE DB-HR (Ruiz, Delgado, Neila, & Vega, 2012).…”
Section: State Of the Artmentioning
confidence: 93%
“…Some authors consider a ventilated air cavity does not necessarily decrease the sound reduction acoustic performance of double walls. 11 In a first measurement campaign carried out ‘in situ’ on a real façade of an existing building where a LVF had been installed as refurbishing solution for a previous masonry façade, 12 it was found that sound insulation against airborne noise was not dramatically affected by the moderate ventilation proposed in the European Construction Codes for hygrothermal control purposes. This aspect should be considered in the renovation of existing building facades.…”
Section: Introductionmentioning
confidence: 99%
“…(Barbero Barrera, 2011;Barrero et al, n.d.;Cuerda Barcaiztegui & Neila González, 2012;Demirbilek & Yener, 1996;Lidelöw et al, 2019c;Perier, 1853) (Barbero- Barrera et al, 2014;Olivieri, 2013;Olivieri et al, 2009Olivieri et al, , 2014Rivera et al, 2017;Ruiz et al, 2012) (Camino Olea, 2001;Lucas Bonilla et al, 2021;Montalban Pozas, 2015;Muriel Holgado et al, 2021;Olea & Montoro, 2014;Pozas & Espada, 2016;Ramos Gavilán et al, 2018;Villegas et al, 2018)…”
mentioning
confidence: 99%